Linear Array Design with Switched Beams for Wireless Communications Systems - Vinícius Ludwig-Barbosa; Edson Schlosser; Renato Machado; Filipe Guterres Ferreira; Sabrina Müller Tolfo; Marcos Vinício Thomas Heckler (International Journal of Antennas and Propagation)
This paper presents an analysis for optimal design of switched beamforming applied to a linear array for wireless communication systems. The beam switching scheme provides coverage of a given sector in azimuth and controls the sidelobe level simultaneously. The analysis was developed considering arrays composed of Quasi-Yagi elements. The model assumes a user moving in the azimuthal direction under a constant velocity and with an estimation of the signal-to-noise ratio (SNR) at the mobile user (MU). The radio base station applies the beam that yields the best performance during transmission. The decision is based on the feedback information received from the MU. The goal of the analysis is to determine the best trade-off between the array size and number of feedback bits necessary to maximize the SNR at the receiver. The results show that a compromise between the number of beam-pointing directions and the array size should be taken into consideration for a wireless communication system design.